FIQH MUAMALAH IN SHARIA CAPITAL MARKET IN INDONESIA: A LITERATURE REVIEW - Rizal, Muhammad; Soemitra, Andri (Islamic Banking & Economic Law Studies (I-BEST), 2022)
The Islamic capital market is a reality and a current phenomenon amid Muslim life, as a means of muamalah whose transactions do not contain usury, speculation, garar (obscurity), and fraud. This study aims to map the main themes discussed in the Islamic capital market, using qualitative methods with content analysis sourced from articles in the Google Scholar database. The data was obtained using the Publish or Perish (PoP) application for a period of 18 years (2004-2022) with the keywords Islamic capital market, accessed on May 21, 2022, 202 articles (population) were obtained, and 40 articles were taken as samples, while the data collection analysis of 35 articles. The results of the study found that the most widely disclosed themes were 1) Islamic capital market products 25.35%; 2) Current issues 25.35%; 3) History and development; 21.3% 4) Fiqh Muamalah; 18.31% 5) Fatwa of DSN MUI 9.85%. The author of the article states that the capital market is in line with Islamic law in the field of muamalah. In its operation, speculators will inevitably act contrary to Islamic law, which can destroy capital market institutions and economic stability. In realizing the goals of sharia, grounding the capital market is done by cleaning up speculative practices. The current Islamic capital market has become a vital means of the modern economy that products must be developed and invites investors with integrity to Islamic law.